2019
DOI: 10.2147/ijn.s196472
|View full text |Cite
|
Sign up to set email alerts
|

<p>Shape-dependent antimicrobial activities of silver nanoparticles</p>

Abstract: Purpose: An important application of silver nanoparticles (Ag NPs) is their use as an antimicrobial and wound dressing material. The aim of this study is to investigate the morphological dependence on the antimicrobial activity and cellular response of Ag NPs. Materials and methods: Ag NPs of various shapes were synthesized in an aqueous solution using a simple method. The morphology of the synthesized Ag NPs was observed via TEM imaging. The antimicrobial activity of the Ag … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(114 citation statements)
references
References 27 publications
4
92
0
2
Order By: Relevance
“…Apart from size and concentration, the shape of nanoparticles also matters for their antibacterial activity. In separate reports, Penders et al and Cheon et al proved the dependency of antimicrobial activity on the shape of AuNPs and AgNPs respectively [ 75 , 76 ]. Penders et al prepared gold nanospheres (AuNS), gold nanostars (AuNSts) and gold nanoflowers (AuNFs) and checked their activity against S. aureus biofilm.…”
Section: Interaction Of Gold and Silver Nanoparticles With Biofilmmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from size and concentration, the shape of nanoparticles also matters for their antibacterial activity. In separate reports, Penders et al and Cheon et al proved the dependency of antimicrobial activity on the shape of AuNPs and AgNPs respectively [ 75 , 76 ]. Penders et al prepared gold nanospheres (AuNS), gold nanostars (AuNSts) and gold nanoflowers (AuNFs) and checked their activity against S. aureus biofilm.…”
Section: Interaction Of Gold and Silver Nanoparticles With Biofilmmentioning
confidence: 99%
“…The authors speculated that AgNS releases higher amounts of silver ions, which interact with planktonic bacteria and kill them. Thus, as compared to AgNDs and AgNTr, which had lower surface areas and thus lower rates of silver ion release, AgNS had the highest activity [ 76 ]. In all aforementioned reports, the authors also showed a concentration-dependent rise in nanoparticle activity against bacteria [ 73 , 74 , 75 , 76 ].…”
Section: Interaction Of Gold and Silver Nanoparticles With Biofilmmentioning
confidence: 99%
“…For example, the antibacterial effect of nanoparticles has previously been presented to be superior in the case of smaller dimension NPs in studies against different bacterial and fungal lines [126][127][128]. At the same time, spherical nanoparticles have been shown to possess a superior antimicrobial potential compared with cubical, plate-shaped or triangular nanoparticles [126,129].…”
Section: Recent Findings In the Morphology-properties Correlationmentioning
confidence: 99%
“…Влияние формы НЧ при антимикробном воздействии определяется механизмом этого действия. В тех случаях, когда контакт клеточной стенки и НЧ влечет за собой необратимые разрушения (действие активных форм кислорода (АФК), повреждения при миграции энергии при плазмонном резонансе), более выраженный эффект достигается наличием развитой поверхности [41][42][43]. При фотодинамической или фототермической терапии с использованием инфракрасного лазерного излучения предпочтительно использовать НЧ с настраиваемым плазмонным резонансом в окне прозрачности тканей при 750−900 nm, и первым выбором в этом случае являются наностержни [44,45].…”
Section: Discussionunclassified